ARRANJO PRODUTIVO LOCAL APL COLHEITA: COMPETÊNCIAS E APTIDÕES TECNOLÓGICAS ESTRATÉGICAS - Weisner, Aline; Büttenbender, Pedro L.; Zamberlan, Luciano; Sparemberger, Ariosto; Wagner, Adriano (Salão do Conhecimento, 2013)
Resumo